Valorization of Moroccan Cedrus atlantica sawdust: total phenolic, flavonoid contents and antioxidant activity of the hydroalcoholic extracts: Cedrus atlantica sawdust - Harhar, Hicham; BOUYAHIA, Chaimaa; SLAOUI, Miloudia; GOUITI, Mohammed; OUASSOR, Ihssane; ELHAJJAJI, Souad (Polish Journal of Natural Sciences, 2022)
This study was conducted to determine the total polyphenol, flavonoid contents and the antioxidant activity by DPPH (2,2-diphenyl-1-picryl hydrazyl) and ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging effect of hydroalcoholic extracts of Cedrus atlantica (Pinaceae). Two synthetic antioxidants are used as standards; the ascorbic acid and trolox. The wood extracts by Soxhlet, Maceration and Ultrasound of C. atlantica had a high antioxidant capacity. The results of the antioxidant activity by DPPH and ABTS radical scavenging indicated better activities for the Soxhlet extract (IC50 = 163,08 and 134,385 µg/ml respectively) than for the Maceration (IC50 = 348,88 and 473,166 µg/ml respectively) and the Ultrasound extracts (IC50 = 501,47 and 923,902 µg/ml respectively) compared to the standards: ascorbic acid and Trolox (IC50 = 10,278 and 30,154 µg/ml respectively). The total polyphenol and flavonoid content of the extracts by Soxhlet, Maceration, and Ultrasound methods revealed that the Ultrasound extract (187,835 and 37,2 mg EQ/g respectively) had higher polyphenol and flavonoid content than the Soxhlet (157.731 and 6,4 mg EQ/g respectively) and Maceration (123.298 and 29,2 mg EQ/g respectively) extracts.